ANALISIS KONTROL SOSIAL GURU PADA PELANGGARAN TATA TERTIB SISWA KELAS XI DI SMA NEGERI 3 BUNGO - Fatimah Harahap; Firman; Muhammad Ichsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to determine the forms of social control of teachers that are preventive, coercive, curative applied to class XI students at SMA Negeri 3 Bungo; and to analyze the factors causing class XI students at SMA Negeri 3 Bungo to commit violations of discipline. The type of research is qualitative research. Through the sampling technique using Purposive Sampling so that the sample obtained is: PPKn Teacher, BK Teacher, Homeroom Teacher, Class XI Students, and Student Affairs Teacher. Research data was obtained by conducting observations, interviews, and documentation. After all has been obtained, the data was analyzed qualitatively with 3 stages, namely: data reduction, data presentation, and drawing conclusions. The results of the study indicate that the social control of teachers at SMA Negeri 3 Bungo that is applied: preventive, through socialization of rules and advice, but is hampered by the crisis of teacher role models; coercive, through a point system and raids that tend to produce temporary compliance due to the perception of injustice in the enforcement of sanctions; and curative, through tiered coordination and parental involvement which has proven to be the most effective in providing a deterrent effect. Factors causing students to violate discipline include external factors such as weak role models and less conducive classroom environments, as well as internal factors such as low student trust in the confidentiality of guidance counselors and the strong influence of peer group solidarity.